Graph Drawing
DOI: 10.1007/978-3-540-70904-6_12
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Graphs Simultaneously with Fixed Edges

Abstract: Abstract. We show that a planar graph and a tree can always be simultaneously embedded with fixed edges and that two outerplanar graphs generally cannot.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 9 publications
0
33
0
Order By: Relevance
“…Erten and Kobourov [3] showed that any pair of a tree and a path always has a simultaneous embedding with fixed edges. Di Giacomo and Liotta [2] extended this result by showing that any pair of an outerplanar graph with a cycle has a simultaneous embedding with fixed edges while Frati [6] showed that any pair of a planar graph and a tree has a simultaneous embedding with fixed edges. Fowler et al [5] used Frati's result as a starting point to characterize the set of planar graphs that have a simultaneous embedding with fixed edges with any planar graph in two ways: by a forbidden minor and by a complete list of graphs with this property.…”
Section: Introductionmentioning
confidence: 99%
“…Erten and Kobourov [3] showed that any pair of a tree and a path always has a simultaneous embedding with fixed edges. Di Giacomo and Liotta [2] extended this result by showing that any pair of an outerplanar graph with a cycle has a simultaneous embedding with fixed edges while Frati [6] showed that any pair of a planar graph and a tree has a simultaneous embedding with fixed edges. Fowler et al [5] used Frati's result as a starting point to characterize the set of planar graphs that have a simultaneous embedding with fixed edges with any planar graph in two ways: by a forbidden minor and by a complete list of graphs with this property.…”
Section: Introductionmentioning
confidence: 99%
“…Many approaches have been made to decide the problem for some classes of graph pairs [4,7,9,10]. Frati [10] showed that trees and planar graphs always have a SEFE.…”
Section: Introductionmentioning
confidence: 99%
“…Frati [10] showed that trees and planar graphs always have a SEFE. Fowler et al [9] improved this result to show that forests, circular caterpillars (removal of all degree-1 vertices yields a cycle), K 4 , and subgraphs of K 3 -multiedges (an edge (x, y) with any number of edges with x or y as endpoints) are the only graphs to always have a SEFE with any planar graph.…”
Section: Introductionmentioning
confidence: 99%
“…These negative results motivated the study of relaxations of simultaneous geometric embeddings. One possibility is to introduce bends along the edges [4,8,9,13], another, to allow that the same vertex occupies different locations in the two drawings [2,3], introducing ambiguity in the mapping.…”
Section: Introductionmentioning
confidence: 99%